2012
DOI: 10.1111/j.1834-7819.2011.01660.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of computer display performance on the quality of digital radiographs: a review

Abstract: Radiography makes an essential contribution to the processes of examination, diagnosis and treatment planning in dentistry. While the use of film-based imaging still predominates in dentistry, digital imaging is gaining wider acceptance and the use of this modality is anticipated to expand in the future. Two concerns associated with this transition have been raised in the literature. The first of these is the dissatisfaction experienced by many dental professionals with quality of digital radiographs when comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 30 publications
(68 reference statements)
0
15
0
Order By: Relevance
“…Primary displays are used when reading images for the purpose of diagnosis, whereas secondary displays are used for reviewing images for purposes other than diagnosis -for example, the review of images by a referring clinician when a radiologist report has been provided. 9 Primary displays are often dedicated medical display devices, whereas secondary displays are often consumer-grade computer displays. An L max of .350 cdm 22 is recommended for primary displays with the Figure 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary displays are used when reading images for the purpose of diagnosis, whereas secondary displays are used for reviewing images for purposes other than diagnosis -for example, the review of images by a referring clinician when a radiologist report has been provided. 9 Primary displays are often dedicated medical display devices, whereas secondary displays are often consumer-grade computer displays. An L max of .350 cdm 22 is recommended for primary displays with the Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…8 It is also well recognized that display performance will degrade with increasing time in use, which in turn may degrade diagnostic performance. 9 The display characteristics of the iPad have been previously reported. 10 However, there has been no evaluation of the effect of time in use on the display performance of the iPad.…”
Section: Introductionmentioning
confidence: 99%
“…This method ensures that each shade of grey in the transition from white to grey is perceptually linear by taking into account the ability of the human visual system for light, dark and chromatic adaption, preventing two shades of grey from being too close together perceptually. Studies have indicated that calibration using DICOM Part 14 GSDF for radiology displays results in better observer performance, and much of the research in digital radiology is based around compliance to these standards …”
Section: Guidance and Recommendationsmentioning
confidence: 99%
“…To capture the market, dentally configured medical-grade monitors are available that have been engineered to the resolution and grey scale of dental radiographs. 15 16 17 However, conflict is evident throughout the literature regarding their benefit for radiographic diagnostics over off-the-shelf monitors. 2 4 5 6 9 15 16 18 19 20 21 …”
Section: Introductionmentioning
confidence: 99%